(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Secondary school students are the members of generation Z, while their teachers mostly belong to gen X and baby-boomers. Members of the latter groups learnt how to use digital technology and the internet in their young adulthood; on the other hand, generation Z was born in the digital world. Due to this fact, their expectation on the future and their attitude are completely different from that of the older generations, not to speak about their values and priorities. Their parents and teachers, who belong to the older generations, many times have difficulty to understand these attitudes and values, and they are more likely to negatively describe Z-ers with stereotypes. The purpose of the research was to map and describe secondary school students’ opinions: to what extent they agree with stereotypes often uttered by the oldergenerations; moreover, what they think of their parents’ generation. The self-administered anonymous digital questionnaire was shared on the sites of the social media.